A novel multiple signal amplifying immunosensor based on the strategy of in situ-produced electroactive substance by ALP and carbon-based Ag-Au bimetallic as the catalyst and signal enhancer - Zhang, Si; Li, Renkai; Liu, Xiaoying; Yang, Liuqing; Lu, Qiujun; Liu, Meiling; Li, Haitao; Zhang, Youyu; Yao, Shouzhuo (Biosensors & bioelectronics, 2017)
In this work, a novel immunosensor was constructed based on the alkaline phosphatase (ALP) in situ generating an electroactive substance by enzymatic hydrolysis the inactive substrates. The new signal-amplified strategy for sensitive detection of HIgG was based on the catalytic oxidation of ALP-generated products, ascorbic acid (AA), using carbon-based Ag-Au bimetallic as the catalyst and signal enhancer. Through a sandwich reaction, ALP-Ab2 bioconjugates were captured on the electrode surface and the amplified signal can be obtained as follows: the ALP catalyzed the inactive substrate L-ascorbic acid 2-phosphate (AAP) to in situ produce AA; AA as an electroactive product then can be directly electro-oxidized to generate electrochemical signal; At the same time, AA could be catalytic oxidized by Ag-Au bimetallic and resulted in the amplification of electrochemical signal; Finally, the oxidation of Ag on the Ag-Au bimetallic maybe further enhance the detection signal. The proposed immunosensor achieved good linear in the range of 0.005–100ngmL−1 with the detection limit of 0.0009ngmL−1 (S/N =3). The proposed immunosensor was successfully applied in the analysis of human IgG in real samples and got satisfied results. The present work demonstrates a general strategy for the design of multifunctional nanomaterials based on carbon-based bimetallic nanoparticles for different applications, such as biosensors, immunosensors and nanocatalysts. [Display omitted] •A signal amplifying immunosensor based on MWCNTs-AuNPs and Ag-Au was constructed.•ALP can in situ generate an electroactive substance by enzymatic hydrolysis the substrates.•Carbon- based Ag-Au bimetallic act as the catalyst and signal enhancer for detection.•The synergetic of enzyme catalysis and bimetallic enhancement make the signal amplified.•The immunosensor has been successfully applied in the analysis of HIgG in real samples.